Comparison of shear bond strength of etch and rinse, self-etch adhesive system followed by flowable composite resin, and self-adherent composite resin - Zakaria, Myrna Nurlatifah; Suri, Yuyun Andina; Soerachman, Badi; Shariff, Khairul Anuar; Cahyanto, Arief (Padjadjaran Journal of Dentistry, 2020)
Introduction: The adhesive system strongly influences the bond strength of resin composite to the tooth surface. Aside from the commonly used etch and rinse, and self-etch adhesive system and a new approach called self-adherent composite resin to combine the adhesive system to the composite material. This study was aimed to compare the shear bond strength of two adhesive systems, (etch and rinse, self-etch adhesive system) followed by application of a flowable composite resin to a self-adherent resin composite. Methods: This study was experimental consisted of three groups of treatment, G1 (etch and rinse adhesive system+composite resin); G2 (self-etch adhesive system+composite resin), and G3 (self-adherent composite resin). Samples were 27 dentinal surfaces from premolar teeth bonded to composite resin (3 mm diameter and 3 mm in height), according to ISO technical specification No 11405. Shear bond strength test was performed using Universal Testing Machine (UTM) under the load of 50 kgf, and the crosshead speed of 0.5 mm/min, and the data was analysed by one-way ANOVA afterwards. Results: The highest bond strength to dentin was seen in Group 1 (14.89 MPa) followed by Group 2 (11.65 MPa) and Group 3 (11.22 MPa) with no significant difference between the three groups p value =0.117 (p>0.05). Conclusion: The etch and rinse adhesive system had the highest shear bond strength to dentin, followed by the self-etch and the self-adherent composite resin. However, the shear bond strength of all tested groups was comparable.